Investigating the Strategies Used to Translate English Advertisement Slogans into Arabic - AYADI, Amina (Journal of Human Sciences, 2018)
This paper deals with a text-specific translation. It covers the translation of a non-literary text which falls under the subject field of marketing. It aims at investigating the translation strategies used in the translation of advertisements as a recent orientation in the field of translation, which is advertisements’ translation. The paper is composed of a theoretical aspect and a practical one. The theoretical aspect, introduces an overview of translation (translation studies) notably; specialised translation, the translation of a text-specific nature in the field of advertising is, then, introduced and defined, as well as the translation strategies and techniques used for rendering this type of items. In the practical aspect, the translation strategies used to render English advertisement slogans into Arabic are investigated by means of a corpus of English slogans (comparable component) with their Arabic counterparts (parallel component). Their analysis is conducted to provide information about thequantity (frequency of the translation methods used in this context) and quality of these translating methods.